2018
DOI: 10.1111/ijfs.13810
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency and comparison of novel techniques for cell wall disruption in astaxanthin extraction from Haematococcus pluvialis

Abstract: Summary The efficiency of various techniques pulsed electric field (PEF), ultrasound (US), high‐pressure microfluidisation (HPMF), hydrochloric acid (HCl) and ionic liquids (ILs) for cell wall disruption in astaxanthin extraction from Haematococcus pluvialis was compared. The results indicated that ILs, HCl and HPMF treatment were shown the most efficient for cell disruption with more than 80% astaxanthin recovery. While the cell wall integrity of H. pluvialis cyst cell was less affected by US and PEF treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…Therefore, lots of efforts have been done to find new methods to extract vegetable and fruit bioactive compounds effectively and environmental friendly. Different novel and non-conventional extraction methodshavebeenstudiedinrecentyears(JaramilloSánchezetal., 2018; Leong et al, 2015;Liu et al, 2018;Wang et al, 2016). Such as PEF Yun et al, 2017),high hydrostatic pressure Yu et al, 2018), ultrasounds (Ma et al, 2008), microwaves (Teh et al, 2015).…”
Section: Practical Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, lots of efforts have been done to find new methods to extract vegetable and fruit bioactive compounds effectively and environmental friendly. Different novel and non-conventional extraction methodshavebeenstudiedinrecentyears(JaramilloSánchezetal., 2018; Leong et al, 2015;Liu et al, 2018;Wang et al, 2016). Such as PEF Yun et al, 2017),high hydrostatic pressure Yu et al, 2018), ultrasounds (Ma et al, 2008), microwaves (Teh et al, 2015).…”
Section: Practical Applicationmentioning
confidence: 99%
“…Therefore, lots of efforts have been done to find new methods to extract vegetable and fruit bioactive compounds effectively and environmental friendly. Different novel and non‐conventional extraction methods have been studied in recent years (Jaramillo Sánchez, Garcia Loredo, Contigiani, Gómez, & Alzamora, ; Leong, Oey, Clapperton, Aganovic, & Toepfl, ; Liu, Zeng, Cheng, Liu, & Aadil, ; Wang, Zeng, Brennan, Brennan, & Han, ). Such as PEF (Aadil et al, ; Yun, Zeng, Brennan, & Liu, ), high hydrostatic pressure (Wang, Chen, et al, ; Yu et al, ), ultrasounds (Ma et al, ), microwaves (Teh, Niven, Bekhit, Carne, & Birch, ).…”
Section: Introductionmentioning
confidence: 99%
“…HCL Pretreatment was measured through the method of Sarada et al (2006) reported earlier by Liu et al (2018).…”
Section: Hcl Pretreatmentmentioning
confidence: 99%
“…Light microscopy and scanning electron microscopy (SEM) SEM analysis was done according to the method of Wang et al (2016) earlier reported by Liu et al (2018).…”
Section: Raman Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation